Milk yield, quality, udder traits and lamb growth in Lalahan sheep, a new crossbred genotype - Senyuz, HH; Ergiden, Y; Yildirim, Ç; Parildar, ÖO; Coner, FI; Firdolaş, S; Coşkun, MI; Odabaş, E; Mizrak, F; Zengin, Y; Erol, H; Kara, K; et al. (Journal of the Hellenic Veterinary Medical Society, 2025)
The Lalahan sheep is a new genotype developed to suit the steppe conditions of lamb production in Turkey. It is important to determine the milk yield and quality of this new genotype to produce high-quality lamb meat. Additionally, the ewes can also be utilized for milk production under steppe conditions. This study evaluated the milk yield, milk quality, udder characteristics, and lamb growth of the Lalahan genotype. Milk yield traits were assessed based on lactation number (LN) and lactation month (LM). The lambs were divided into two groups during the suckling period: the maternal milk feeding group (M) and the maternal milk with creep feeding group (CF). The daily milk yield for ewes with LN 1, 2 and 3 was 0.406±0.02, 0.560±0.05 and 0.446±0.02 kg, respectively (P<0.001). Similarly, the lactation milk yield for the same groups was 61.19±3.14, 83.49±7.47 and 65.39±3.73 kg, respectively (P<0.001). The udder characteristics showed significant differences (P<0.01, P<0.001) with LM. Milk’s chemical composition, including fat, protein, lactose, and dry matter, changed significantly (P<0.05, P<0.01, P<0.001) due to LN and LM. Most of the fatty acids did not differ significantly among the LN, but they generally differed significantly (P<0.05, P<0.01, P<0.001) due to the LM. Half of the total fatty acids were composed of C16:0 + C18:1 acids, and the mean UFA ratio was 23.70±0.31% throughout lactation. The levels of PUFA, w3, and w6 gradually increased throughout lactation (P<0.001). Except for 180 days (P<0.001), there were no significant differences (P>0.05) in the growth performance of the lambs during the suckling period between the M and CF groups. As a result, the study revealed that the milk yield of Lalahan sheep is comparable to that of local meat-type sheep breeds. Their udder type is suitable for machine milking and milk quality is comparable in terms of fatty acids and milk constituents.